Konsep Keadilan Administratif Dalam Pelayanan Publik Berbasis Perizinan Amdal - Rumuat, Michelle (AL-DALIL: Jurnal Ilmu Sosial, Politik, dan Hukum, 2024)
Article 1 paragraph (3) of the 1945 Constitution eculted that Indonesia was a rule of law. Thus, there is a correlative relationship between the administration of government that must be based on law and the state based on law. Pancasila as an ideology is binding as the value system of the Indonesian nation. One important thing in the continuity of a human civilization is the environment. His sustainability greatly had a big influence and immediately had an impact on living things in it. Indonesia has adapted the Rio Declaration which talked about the struggle for environmental preservation. In addition, implementing and upholding the law regarding preservation efforts is the joint responsibility of humanity. The right to a good and healthy environment, listed in Article 28 h of the 1945 Constitution (1945 Constitution. The number of human activities in various sectors that are in direct contact and directly impact on the environment is important to continue to think about the issue of environmental preservation. In the licensing process of all human activities, especially in the industrial field, it is mandatory through the process of analysis of the environment (AMDAL). Indonesia? And how are the obstacles for the government as a servant of the public able to realize administrative justice in public service based on AMDAL licensing?